The actin-bundling protein, PLS3, is part of the mechanoresponsive machinery that regulates osteoblast mineralization - Chin, Samantha M.; Unnold-Cofre, Carmela; Naismith, Teri; Jansen, Silvia (Frontiers in Cell and Developmental Biology, 2023)
Plastin-3 (PLS3) is a calcium-sensitive actin-bundling protein that has recently been linked to the development of childhood-onset osteoporosis. Clinical data suggest that PLS3 mutations lead to a defect in osteoblast function, however the underlying mechanism remains elusive. To investigate the role of PLS3 in bone mineralization, we generated MC3T3-E1 preosteoblast cells that are stably depleted of PLS3. Analysis of osteogenic differentiation of control and PLS3 knockdown (PLS3 KD) cells showed that depletion of PLS3 does not alter the first stage of osteoblast mineralization in which a collagen matrix is deposited, but severely affects the subsequent mineralization of that matrix. During this phase, osteoblasts heavily rely on mechanosensitive signaling pathways to sustain mineral deposition in response to increasing stiffness of the extracellular matrix (ECM). PLS3 prominently localizes to focal adhesions (FAs), which are intricately linked to mechanosensation. In line with this, we observed that depletion of PLS3 rendered osteoblasts unresponsive to changes in ECM stiffness and showed the same cell size, FA lengths and number of FAs when plated on soft (6 kPa) versus stiff (100 kPa) substrates in contrast to control cells, which showed an increased in each of these parameters when plated on 100 kPa substrates. Defective cell spreading of PLS3 KD cells on stiff substrates could be rescued by expression of wildtype PLS3, but not by expression of three PLS3 mutations that were identified in patients with early onset osteoporosis and that have aberrant actin-bundling activity. Altogether, our results show that actin-bundling by PLS3 is part of the mechanosensitive mechanism that promotes osteoblast mineralization and thus begins to elucidate how PLS3 contributes to the development of bone defects such as osteoporosis.